The level of dentist’s knowledge regarding the role of radiology in the field of forensic odontology in Makassar: Tingkat pengetahuan dokter gigi umum mengenai peranan radiologi di bidang odontologi forensik di Makassar - Y, Muliaty; Kalsum, Andi Amirrah (Makassar Dental Journal PDGI Makassar, 2025)
A general dentist can be asked to assist in investigating incidents and disasters through dental identification in forensic odonto-logy. Radiography is often used because it is relatively easy and more economical. This article explores the knowledge of gene-ral dentists in Makassar regarding the role of radiology in forensic odontology. Through descriptive observational research with a cross-sectional design, data was collected from 50 general dentists practising in Makassar. A questionnaire was used to measure the general dentists' knowledge, consisting of 20 closed questions; a score of 1 was given for correct answers, and a score of 0 was given for incorrect answers. The data from the respondents' answers were divided into three knowledge categories: 50% of respondents had good knowledge, 46% had sufficient knowledge, and 4% had poor knowledge. It was concluded that 50% of general dentists in Makassar had good knowledge about the role of general dentists in forensic odontology.